Estimation of line capacity of single-track section of Baikal-Amur Mainline using mass service theory - M. L. Zharkov; A. L. Kazakov; A. V. Suprunovsky (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The research is intended to assess the line capacity of the Severomuisky Section of the Baikal-Amur Mainline (BAM). The selected section is typical for the BAM and consists mainly of single-track sections. One of the stations is a sectional station (where the type of locomotive traction is changed), the section has tracks through a mountain pass and a tunnel, which enables several train traffic routes. Separate stations generally perform uniform operations, such as stop and non-stop make way, technical inspection, change of crews, as well as make way on sections. At the same time, their duration is affected by random external influences, such as weather, breakdowns, and human factor.Materials and methods. The authors use methods of mathematical and computer modelling and apply the mass service theory to build a mathematical model of traffic working along the section. It studies objects where uniform operations are regularly performed and their duration is not deterministic. Such objects include railway systems. Simulation modelling was used to analyze the resulting models.Results. The researchers built a mathematical model of train traffic along the Severomuisky section in the form of a mass service network with two request inflows. It is used to conduct a number of computational experiments. Their results identified bottlenecks in the section infrastructure and assessed the effectiveness of the partial batch train time-table on the section.Discussion and conclusion. The authors found that the Severomuisky Section now has a line capacity reserve, and its train traffic may be increased from the current 23 to 27 pairs of trains per day. The studies show that partial batch timetable reduces train delays on the section but requires upgrades to some stations and does not allow for an increase in train traffic above the designated level. Thus, it is concluded that partial batch time-table on this section is inexpedient, and a significant (by times) increase in its line and traffic-carrying capacity requires the creation of a double-track service.